E-Government Strategies as a Modern Perspective of Learning Organizations: Practical Study in the Directorate of Work-Iraq of Anbar - Naser Mohammed, Khamees; Tume Atua, Tarek (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT   E-government has become a high priority program for government organizations at the central and regional levels around the world. The follow-up of certain clear brand strategies by e-government organizations can motivate a learning organization to improve its characteristics. The authenticity of the study has been examined through the use of total examination forms (178) compiled from officials of the Iraqi traffic management in Anbar. The results strongly support the suggested model and refer the presence of a positive relationship and its effects between e-government strategies and the characteristics of learning organizations.